Determining research priorities for adolescent and young adult cancer in Australia. (12th February 2015) - Medlow, S.; Patterson, P.
<x xml:space="preserve">Abstract</x> The Australian Youth Cancer Service (YCS) is part of a growing international movement to provide advocacy and better targeted health‐care services for adolescents and young adults (AYAs) with cancer. One of the key initiatives of the YCS is to determine and implement priorities within Australian AYA cancer research. The YCS used the value‐weighting online survey technique of allocating 100 hypothetical units of funding across pre‐determined topics of research in order to determine Australian consumers' and health professionals' AYA cancer research priorities. A total of 101 participants (26 consumers and 75 health professionals) took part in the online survey. Biomedical and Clinical Medicine Research was allocated the greatest proportion of available funding. A number of priority populations were also identified, although these were distributed across pre‐treatment and post‐treatment stages. The preferences of consumers and health professionals to invest available AYA cancer research funds in Biomedical and Clinical Medicine Research will be an important consideration in guiding the Australian YCS decision‐making process in the immediate future. 'Prevention, screening and early detection' was also an important research funding target, along with survivorship populations.